Photoconverters with microrelief p-n-junction on a basis of p AlxGa₁₋x-p GaAs-n GaAs-n⁺ GaAs heterojunction - Karimov, A.V.; Yodgorova, D.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Given in this work are the results of studying the process of creation of diffusion and epitaxial layers in microrelief structures. It has been shown that photoconverting structures with a microrelief interface were different in their efficiency under the used level of the illumination intensity.